Consultation frequencies in general practice. - Kilpatrick, S J (1977)
Some models of the process by which individuals seek medical care suggest the negative binomial as the underlying distribution of the frequencies of consultations in a given practice. Data from the 1970-71 National Morbidity Survey of General Practice are used to test these competing models. It is shown that the negative binomial distribution successfully fits consultation frequencies in aggregate and in subdivisions according to age, sex, and duration of registration. In this article is is assumed that the consultation process has two components: the patient's decision to visit his doctor for a new illness and the follow-up visits that results from this new problem. Supplementing previous evidence that the distribution of episodes of new illnesses follows a negative binomial distribution, this article shows that consultation frequencies among individuals presenting with one new illness also follow a negative binomial distribution. A unifying model is required to synthesize these findings.